Road Projects Cost Benefit Analysis : Scenario Analysis of the Effect of Varying Inputs - Tsunokawa, Koji (World Bank, Washington, DC, 2017)
Six projects from six countries were selected as the cases for detailed analysis in this study. They are from Argentina, Botswana, India, Kenya, Lao PDR and Paraguay, representing a wide range of geographical distribution. Also, the extent of the effect of economic downturn which these countries experienced ranges a wide variety. In an economic downturn, uncertainties increase with many inputs of road projects Cost Benefit Analysis (CBA), including fuel prices, levels of demand, investment costs and maintenance availability. Also, important parameters of project evaluation such as discount rate and value of time need to be more carefully scrutinized. Therefore, it is very important for the developing countries to have good understanding about the effects of the variability of these inputs/parameters on project viability and the ranking of road investments. It is a role of the developing agencies to conduct a systematic analysis of these effects and disseminate the findings and knowledge obtained. The objective of the study is to obtain insights regarding the effects of varying inputs and parameters on the viability of road projects through case studies using Highway Development and Management Model (HDM-4), thereby to facilitate the formulation and implementation of road projects that increase the welfare of the society under the environment of increased uncertainty in an economic downturn. The results of the study will be summarized in a transport note as a discrete knowledge product and disseminated among various stakeholders including developing agencies staff, government officials and donor communities. To assess the effects of increased uncertainty with inputs of cost benefit analysis on the economic viability of road projects, this study first investigated the range of variability of the inputs for the six selected projects/countries. It was found that the variability ranges differ by country reflecting the degree of decrease in transport demand and relative change in factor prices due to economic downturn.